Analisa Profit Margin Produk Sampingan : Minyak Kelapa Kuning Di Kampung Martewar Sarmi-Papua - Hesti Helen Maniagasi; Sarah Usman; Robert Tataming (Universitas Negeri Surabaya, 2025)
This study aims to analyse the profit margin of yellow coconut oil (Coconut Cooking Oil/CCO), a by-product of coconut processing, to assess its business feasibility and sustainability based on local resource potential. The research employs a descriptive quantitative approach. Data were collected through observation, interviews, and documentation involving five informants from Sarmi Regency. Production cost and profitability analyses were conducted using the variable costing method to calculate production costs, while Net Profit Margin (NPM) was used to measure profitability. The findings indicate that selling CCO in the village market yields a higher average Net Profit Margin than selling in the central market. This difference is primarily influenced by higher selling prices in the village, lower non-production costs, and the absence of transportation expenses. Although production volumes varied among informants, profitability was found to be more strongly affected by cost efficiency and pricing strategies rather than production scale alone. From a managerial perspective, the study highlights the importance of systematic cost recording and classification to improve production efficiency and support informed pricing and marketing decisions. Prioritising local sales channels is recommended to maximise profitability and enhance the sustainability of small-scale coconut processing businesses, aligned with local economic potential